Hybrid Solar-Radiofrequency Energy Harvesting System for Fifth Generation 5G Terminals - Gordón, Carlos (2023)
This paper describes in detail the design and implementation process of a Hybrid Solar-Radiofrequency Energy Harvesting System for Fifth Generation 5G Terminals, in order to take advantage of the energies present in the environment and convert them into electrical energy, the system has two voltage outputs, 9 V and 5 V, that will serve as a power source for different applications. The methodology used consists of 4 stages in which the design, simulation, fabrication and characterization of the stages that conform the system are shown. Operational tests showed that the system works as indicated, during the day the system can fully charge a 9 V battery at 250 mA in approximately 3 h, while the total energy collected during a full night was 560 mV. The voltage outputs vary between 8.86 V and 5.04 V respectively when the battery is charging and 9.11 V and 5.16 V respectively when the battery is fully charged. This work is intended to lay a foundation for future research on hybrid energy harvesting systems.